Hands-on Gross Anatomy Instruction Improves Clinical Imaging Skills Among Cardiovascular Fellows. (April 2019) - O'Leary, JM; McNeely, DE; Damp, JA; Wells, QS; Nanney, L; Mendes, L
Introduction: Multi-modality imaging is a crucial component of cardiovascular (CV) fellowship training and requires knowledge of CV anatomy for interpretation. We hypothesized that hands-on anatomy education would improve the imaging interpretation skills of CV fellows. Methods: The first-year CV fellowship class completed a hands-on cadaveric anatomy session correlated with clinical imaging. Fellows' ability to identify CV structures on cardiac imaging was assessed using a 30-question assessment tool administered at baseline and 1 week and 6 months post intervention. Advanced CV fellows (second or third year) who had not attended the session were also tested. Scores were expressed as median [interquartile range]. Results: Among 9 first-year fellows, the majority reported no formal anatomy training since medical school (N = 7) and rated their knowledge of CV anatomy as fair or poor (N = 7) prior to the intervention. The median assessment score was higher 1 week after intervention vs baseline (24 [23-25] vs 19 [17-21]; P = .013) and remained higher than baseline at 6 months (26 [26-28] vs 19 [17-21]; P = .009). The 6-month post-intervention score for first-year fellows was not significantly different than that of senior fellows (n = 10) not exposed to the intervention (26 [26-28] vs 26 [23-27]; P = .434). Conclusions: Gross anatomy instruction improved first-year CV fellows' interpretation of CV imaging. Anatomic instruction may be a useful adjunct to multi-modality imaging education.